APLIKASI SMART TRY OUT SYSTEM BERBASIS KOMPUTER UNTUK PESIAPAN UNBK SISWA SMK - Dwi Setia Mujiono; Jatmiko Indriyanto (Universitas Muhammadiyah Semarang, 2018)
Various problems faced by students in computer based test caused by the lack of tools to have trial test. This research is aimed to develop Smart Try Out System as a tool of computer based test and to know whether the tool is qualified to measure the students ability. The research method used in this research is Research and Development (RnD). The result of the study showed the response from teachers, media experts, and students. From the teachers, the percentage of the achievement reaches 92% at good qualification. From the media experts, the programming reach 80% at good qualification and the performance reach 76% at good qualification. Response from 10 students, the system reach 82,72% at good qualification. Response from 50 students, the system reach 87, 36% at good qualification. Based on the study, the writer developed a test device named Smart Try Out System which have response at good qualification. Keywords : Computer, Smart Try Out System, UNBK